INSTRUCTION OF NATIONAL AND UNIVERSAL VALUES THROUGH THE HERITAGE OF OUR ANCESTORS IN ORGANIZING A MODERN FAMILY - Sherzodbek Jamolovich SUYUNOV (Scholar Express Journal, 2023)
This article describes the family, education and upbringing issues in it, how to organize a modern family, how to instill education into the family through the heritage of our ancestors, bring it, how to teach the organization of national and universal values in the family, religious and explained from a secular point of view
Keywords: family; society; father; mother